Producing a "Natural" Sound: Interweaving and Differentiating Analog and Digital Audio to Create the Soundscape of a Great Show - Vinck, Dominique; Waeber, Sarah; Tanferri, Mylène (Swiss Journal of Sociocultural Anthropology, 2021)
Based on ethnographic investigation into the sound system of a large-scale performance, the article seeks to understand what happens to digitally processed sound in a situation where the professionals involved are trying to produce a “natural sound”. The investigation pays attention to the ontology of what makes up sound in order to answer the question of its naturalness and how its different materialities contribute to it. The field of investigation is a celebration that has taken place only once a generation, for three centuries, and mobilises several thousand people, including about twenty sound engineers. This article gives an account of sound as a practical achievement, the fruit of multiple conversions, and cleaning operations.